Effects of timing of the antiretroviral therapy initiation on multidrug-resistant tuberculosis outcomes in HIV co-infected patients in Sizwe tropical disease hospital, Johannesburg, South Africa, 2007-2010 - Umanah, Teye Aniefiok (My University, 2015)
Multidrug-resistant tuberculosis (MDR-TB) is a threat to global tuberculosis (TB) control. Its management in human immunodeficiency virus (HIV) co-infected patients has been a challenging experience. There is however paucity of data on the effects of antiretroviral treatment (ART) before or after starting MDR-TB treatment. Therefore the objectives of this study were to describe the clinical characteristics and outcomes of MDR-TB treatment; and determine the predictors of mortality, cure and failure in HIV-TB co-infected patients who were started on ART before and after commencement of MDR-TB treatment.